Efektivitas Pemanfaatan Kelas Ibu Hamil terhadap Pengambilan Keputusan dalam Pelayanan Kesehatan Ibu Anak ( KIA ) di Kabupaten Klaten - YENI NURUL RATMAWATI RATMAWATI; dr. Bima Suryantara, SpOG(K); Dr. Heni Puji Wahyuningsih,S.SiT,M.Keb (Journal of Health (JoH), 2023)
Background : Not yet optimal decision making in maternal and child health services which includes the use of MCH books, antenatal care visits, adherence of pregnant women in consuming iron tablets, Incomplete charging BPCR and self efficacy pregnancy , may be one of the contributing indirecy cause maternal death. One of the government programs to reduce maternal mortality and improve the health of pregnant women is to hold classes for pregnant women. The research objective was to determine the effectiveness of the use of pregnant women’s classes on decision making in maternal and child health services. Methods: The research design used was a true experimental design with a posttest only control design. The research sample was 130 pregnant Results: Classes for pregnant are effective in increasing use of the MCH book, compliance with ANC visits, completeness of BPCR and compliance with taking iron tablets , implementation of classes for pregnant was not effective in increasing self efficacy . The results showed that pregnant who attend classes for pregnant women could increase the MCH by 5,94 times after controlling for the parity variable, can increase adherence to ANC Visits 10,97 times after controlling for age, maternal education and health insurance, can increase the completeness of BPCR by 16,58 times after controlling for the parity variable, can increase adherence to taking iron tablets by 13,82 times after controlling for parity variables Conclusion : implementation of the class for pregnant women is effective in increasing decision making in maternal and chold health services.